An attribute-based and object-oriented approach with system implementation for change impact analysis in variant product design. (May 2015) - Chen, Chung-Yang; Liao, Gen-Yih; Lin, Ku-Shen
Abstract: Variant product design is critical to the continued survival of a product in the demand-changing market. As variant product design involves numerous and concurrent attempts at requirement and product modification, a change impact analysis (CIA) becomes essential in order to capture both the potential and contextual impacts of a change proposal, and thereby ensure the consistency of the product's integrated content throughout the process of carrying out any changes. In this regard, this paper presents an attribute-based, object-oriented approach for effectively and comprehensively performing the CIA tasks in variant product design. This approach models the integrated content of a product by characterizing its components and associated requirements with attributes and linkages. It then features an object-oriented change propagation design in order to handle the dynamic and recursive CIA loops. This approach is also able to show the collective impact when multiple changes are attempted. A computerized prototype, EPCII_EC, is implemented in order to realize the approach, and an illustrative product case with a comparative evaluation is provided in order to validate the work. Issues and limitations of this study are also discussed and suggestions are provided for future studies. Highlights: An integrated product model for identifying contextual impacts of design changes. An OO mechanism for handling dynamic and recursive change propagation processes. A tool to handle multiple change attempts and show the collective impact result.